1996
DOI: 10.1017/s0016672300033449
|View full text |Cite
|
Sign up to set email alerts
|

Esterase polymorphism in insecticide susceptible populations of the mosquitoCulex pipiens

Abstract: Gene amplification involving a particular haplotype has been found at the esterase B locus of mosquitoes from various countries. This similarity has been explained by a unique amplification event followed by migration and selection by organophosphate (OP) insecticides. This assumes that the polymorphism of non-amplified esterase haplotypes is so large that the chance of independent amplification in two distinct populations is negligible. In order to test this assumption, three susceptible populations from nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…At the Ester locus, independent amplifications have occurred only a few times, as indicated by the known list of distinct amplified alleles (Table 2) and the huge polymorphism existing among non-amplified alleles (Raymond, Qiao & Callaghan, 1996). This relatively low number of independent de novo amplification events, inventoried on a world scale for a pest species with large population sizes, indicates that there is somehow a limitation on the rate of occurrence of new advantageous mutation.…”
Section: Frequency Of 'Beneficial Mutations'mentioning
confidence: 99%
“…At the Ester locus, independent amplifications have occurred only a few times, as indicated by the known list of distinct amplified alleles (Table 2) and the huge polymorphism existing among non-amplified alleles (Raymond, Qiao & Callaghan, 1996). This relatively low number of independent de novo amplification events, inventoried on a world scale for a pest species with large population sizes, indicates that there is somehow a limitation on the rate of occurrence of new advantageous mutation.…”
Section: Frequency Of 'Beneficial Mutations'mentioning
confidence: 99%
“…The most prevalent amplified esterase genes are estα2" and estβ2", which occur worldwide [1,14,15]. Some insects have variants of estβ1 (alleles of estβ2") that might or might not have a co-amplified estα3 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sequences in and around the A2 and B2 alleles were mapped using RFLP techniques. Previous work by Raymond et al (1991Raymond et al ( , 1996 demonstrated that the B2 allele had spread worldwide by migration since the restriction maps collected from strains throughout four continents were identical. Similar maps of the A2 allele were constructed.…”
Section: Introductionmentioning
confidence: 99%